Implementasi Layanan Bimbingan Karir Dalam Menstimulasi Kemandirian Anak Tunarungu Di TK SLBN 1 Makassar - Nurismi Asyisa Karim; Sri Wahyuni Asti; Hajerah Hajerah (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Independence is an important aspect in children's development, including children with hearing impairments, because it is the basis for developing the ability to adapt, be responsible, and prepare themselves for life in the future.This study aims to describe the implementation of career guidance services and to identify supporting and inhibiting factors in stimulating the independence of children with hearing impairments at TK SLBN 1 Makassar. This research employed a qualitative descriptive approach. Data sources included the principal, classroom teachers, and children with hearing impairments. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results show that career guidance services were implemented through routine visual-based activities, hands-on practice, and habituation, such as folding clothes, organizing learning tools, washing eating utensils, and planting activities. These activities effectively fostered children’s physical, social, emotional independence, and sense of responsibility. The findings indicate that 60% of children were categorized as Very Well Developed, 20% as Developed as Expected, and 20% as Beginning to Develop. Supporting factors included teacher competence, children’s enthusiasm, visual-based learning, and school environmental support. Meanwhile, inhibiting factors consisted of limited verbal communication, individual differences in abilities, and insufficient learning facilities